Methylation of alpha-synuclein in a Sudanese cohort. (August 2022) - Bakhit, Yousuf; Schmitt, Ina; Hamed, Ahlam; Ibrahim, Etedal Ahmed A.; Mohamed, Inaam N.; El-Sadig, Sarah M.; Elseed, Maha A.; Alebeed, Mohamed A.; Shaheen, Mutaz T.; Ibrahim, Mohamed O.; Elhassan, Ali A.; Eltom, Khalid; et al.
Abstract: Background: Several studies suggested a significant role of epigenetic changes, including alterations in miRNA, histone modifications, and DNA methylation of α-synuclein ( SNCA ) in Parkinson's disease (PD) pathogenicity. As of yet, only very few studies have been carried out in this field in Africa and none in Sudan. Materials and methods: We collected DNA from 172 Sudanese individuals (90 cases, 82 controls) who donated saliva for DNA extraction (mean age of onset: 40.6 ± 22.4 years). A family history of PD was evident in 64 patients. DNA preparation and bisulfite sequencing of SNCA intron1 was performed as described earlier. Results: Of the fourteen analyzed CpGs of SNCA intron1, CpGs 16-23 were hypomethylated in PD (P-value ranged from 0.023 to 0.003). P–values improved, when sporadic cases were excluded from the analysis. Conclusion: We identified the presence of a specific pattern of DNA methylation in a young Sudanese cohort of familial PD, which confirms the importance of the methylation of SNCA intron1 for PD. This phenomenon appears to be independent of ethnicity, the impact of environmental factors, drug history, or familial clustering. Highlights: SNCA expression is linked to SNCA intron1 methylation. Specific pattern of DNA hypomethylation was observed in the Sudanese cohort.